ADAT INSTITUTIONS IN ACEH GOVERNMENT: A CONSTITUTIONAL PERSPECTIVE - Abiyoso, Yunani; Abdillah, Ali; Wasti, Ryan Muthiara; Sujatnika, Ghurnarsa; Fakhri, Mustafa (UI Scholars Hub, 2021)
The existence of adat (customary law) in Indonesia becomes a source of value for the survival of the nation. Each region in Indonesia has different adat that can be used as a reference for the form of governmental system in Indonesia. The 1945 Constitution has recognized the existence of adat government that consisting of various forms of adat that have been adopted long before the 1945 Constitution existed. The existence of adat cannot be separated from national and Islamic values. This research was conducted to find out form of adat institution in Aceh and how the integration of such adat governance in local government system based into national law. Thus, to achieve the objectives, this study was conducted by normative juridical research method with historical approach and comparison with other indigenous peoples in Indonesia.